Chatime Living World Kota Wisata Cibubur, Bogor Business Investigation Using SWOT Analysis - Syamruddin Syamruddin (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
This study aims to investigation the Chatime Living World Kota Wisata business, Cibubur, Bogor. The study used a mixed method. Data analysis techniques include SWOT Analysis, IFE Matrix Analysis, EFE Matrix Analysis, IE Matrix Analysis, SWOT Matrix, and SWOT Analysis Diagram. The results of the study showed that the IFE Matrix strengths and weaknesses with a score of 3.96. Then in the EFE Matrix opportunities and threats with a score of 3.96. Based on the IE Matrix, the position of the company in cell I shows that the appropriate strategy is to grow and develop (growth and build) which means that this strategy is adjusted to the strengths of the company's internal side to take advantage of the right opportunities to gain benefits for the company. While in the SWOT Matrix using the SO, WO, ST, and WT formulas, twenty strategies were obtained. The results of the SWOT Analysis Diagram show that the company is in quadrant I, namely supporting an aggressive strategy.